Moderate mitral regurgitation accelerates left ventricular remodeling after postero-lateral myocardial infarction - Soleimani, Mehrdad (2011)
BACKGROUND: Chronic ischemic mitral regurgitation (CIMR: MR) is associated with poor outcome. However, the effect of CIMR on left ventricular (LV) remodeling after postero-lateral myocardial infarction (MI) remains controversial. We tested the hypothesis that moderate MR accelerates LV remodeling after postero-lateral MI. METHODS/RESULTS: Postero-lateral MI was created in 10 sheep. Cardiac MRI was performed 2 weeks before and 2, 8 and 16 weeks after MI. LV and right ventricular (RV) volumes were measured and regurgitant volume (RegurgVolume) calculated as the difference between LV and RV stroke volumes. Multivariate mixed effect regression showed that LV volumes at end-diastole (ED) and end-systole (ES) and LV sphericity were strongly correlated with both RegurgVolume (p<0.0001, p=0.0086 and p=0.0007 respectively) and %Infarct area (p=0.0156, 0=0.0307, and p<0.0001 respectively). On the other hand, while LV hypertrophy (LV wall volume) increased from 2 to 16 weeks post-MI there was no effect of either RegurgVolume or %Infarct. CONCLUSIONS: Moderate mitral regurgitation accelerates LV remodeling after postero-lateral MI. Further studies are needed to determine whether mitral valve repair is able to slow or reverse MI remodeling after postero-lateral MI.